Investigating the L-Glu-NMDA receptor-H2S-NMDA receptor pathway that regulates gastric function in rats’ nucleus ambiguus - Sun, Hongzhao; Li, Chenyu; Shi, Yuan; Wang, Yiya; Li, Jinjin; Fan, Linkun; Yu, Yan; Ji, Xiaofeng; Gao, Xiaoting; Hou, Keyuan; Li, Yuxue (Frontiers in Pharmacology, 2024)
In previous investigations, we explored the regulation of gastric function by hydrogen sulfide (H 2 S) and L-glutamate (L-Glu) injections in the nucleus ambiguus (NA). We also determined that both H 2 S and L-Glu have roles to play in the physiological activities of the body, and that NA is an important nucleus for receiving visceral sensations. The purpose of this study was to explore the potential pathway link between L-Glu and H 2 S, resulting in the regulation of gastric function.: Physiological saline (PS), L-glutamate (L-Glu, 2 nmol), NaHS (2 nmol), D-2-amino-5-phopho-novalerate (D-AP5, 2 nmol) + L-Glu (2 nmol), aminooxyacetic acid (AOAA, 2 nmol) + L-Glu (2 nmol), D-AP5 (2 nmol) + NaHS (2 nmol) were injected into the NA. A balloon was inserted into the stomach to observe gastric pressure and for recording the changes of gastric smooth muscle contraction curve. The gastric fluid was collected by esophageal perfusion and for recording the change of gastric pH value.Results: Injecting L-Glu in NA was found to significantly inhibit gastric motility and promote gastric acid secretion in rats (P < 0.01). On the other hand, injecting the PS, pre-injection Nmethyl-D-aspartate (NMDA) receptor blocker D-AP5, cystathionine beta-synthase (CBS) inhibitor AOAA and re-injection L-Glu did not result in significant changes (P > 0.05). The same injection NaHS significantly inhibit gastric motility and promote gastric acid secretion in rats (P < 0.01), but is eliminated by injection D-AP5 (P > 0.05).The results indicate that both exogenous L-Glu and H 2 S injected in NA regulate gastric motility and gastric acid secretion through NMDA receptors. This suggests that NA has an L-Glu-NMDA receptor-CBS-H 2 S pathway that regulates gastric function.